PENGGAMBARAN YOUKAI DALAM KESUSASTRAAN JEPANG DARI PERIODE JOUDAI HINGGA MODERN - Retno Dewi Ambarastuti (Universitas Andalas, 2018)
This research is historical literature research focusing on the description of Youkai character in Japanesse literature from the ancient to modern period. Youkai is Japanesse mythology creature in various appearance, and can be visible and invisible haunting the human. This research used descriptive analytical method. The results of the research are 1) Youkai has been well known since it was in Japanesse ancient through religion ritual, 2) In the middle period, youkai was described as misery as the result of Budha influence, 3) In Edo period, youkai was given a name and well known in folktale and legend, and 4) in modern period youkai is persisted as one of the original characters in Japanesse culture, described as in the real life, once metaphorized as an evil, and in modern era, youkai is described as kawaii (cute) character, not only represented in folktale or story but also published in magazines, manga, and anime as well. And then, in modern period, youkai is desribed as a good creature, and sometime it helps human.Key Words: anime, story, historical literature, youkai, kawaii, manga, mythology creature